Applied social research : Sba tool for the human services - Duane R. Monette (Brookscole, 2008)
Presenting the methods of social science research within the context of human service practice, APPLIED SOCIAL RESEARCH, 7e International Edition is the ideal text for courses emphasizing applied research in human services, counseling, social work, sociology, criminal justice, and community planning. Covering the full range of topics included in traditional social science research methods courses, the book shows students the ever-expanding number of ways that research is being applied to practice today, as well as the extensive links between research and practice. In addition, this Seventh Edition features a broader focus on the role of technology in performing research that includes devices such as cell phones and PDAs as well as computers to keep students on the cutting-edge of research technology and ensures that they understand both the benefits and risks of relying on those devices